Stereotaxic Coordinates and Morphological Characterization of a Unique Nucleus (CSF-Contacting Nucleus) in Rat - Song, Si-Yuan; Li, Yue-Hao; Bao, Cheng-Yi; Li, Ying; Yin, Peng-Cheng; Hong, Jia; Li, Wan-Lin; Shi, Yuan; Zhang, Li-Cai (Frontiers in Neuroanatomy, 2019)
A unique nucleus, the cerebrospinal fluid (CSF)-contacting nucleus, has recently been recognized in the brain parenchyma. The outstanding feature of this nucleus is that the neural somas are located in the parenchyma, but their processes stretch into the CSF, implying that it may be a key structure bridging the nervous and body fluids-regulating systems and may play a pivotal role in modulating physiological activities. However, the true biological significance of this nucleus needs to be uncovered. The morphology of a nucleus is one of the most important parameters for neuroscience studies. For this reason, a common experimental animal, Sprague-Dawley (SD) rats, was chosen. The position, adjacent structures, neuronal distribution, size, three-dimensional reconstruction, and core coordinates of the CSF-contacting nucleus in SD rats of different weights (90-400 g) were illustrated for the first time. Furthermore, the formulas for calculating the core coordinates of the CSF-contacting nucleus in rats of different weights were revealed. Finally, the possible biological functions uncovered by past research are reviewed in this paper. This study provides an indispensable methodology and a significant reference for researchers interested in this unique nucleus.